The Effects of Mandatory Prescription Drug Monitoring Programs on Foster Care Admissions - Rania Gihleb; Osea Giuntella; Ning Zhang (Institute of Labor Economics (IZA), 2018)
The opioid epidemic is a national public health emergency. As the number of fa- tal overdoses and drug abuse skyrockets, children of opioid-dependent parents are at increased risk of being neglected, abused or orphaned. While some studies have examined the effects of policies introduced by states to restrict prescription drug supply on drug abuse, there is no study analyzing their effects on children. This paper estimates the effect of must-access prescription drug monitoring programs (PDMPs) on child removals. To identify the effects of the programs on foster care caseloads, we exploit the variation across states in the timing of adoption of must-access PDMPs using an event-study approach as well as standard difference-in-difference models. Consistent with previous evidence examining the effects of PDMPs on drug abuse, we find that operational PDMP did not have any significant effects on foster care caseloads. However, the introduction of mandatory provisions reduced child removals by 10%. Exploring the reasons of removals, we show that these effects are driven by the reductions in cases of child neglect. There is also evidence of significant reductions in removal cases associated with child physical abuse.
Keywords: I12; I18; J13; 330; opioid epidemic